NEW FORM FOR TERRORISM VIS-À-VIS TRAFFICKING AS CRIME IN DISGUISE - Ani Suryani Hamzah (Fakultas Hukum Universitas Mataram, 2013)
The metamorphosed of trafficking crime is on the level of sophisticated, sophistication, so that the crime look “normal” to as if “legal”, the trafficking agents, making the blurring of the crime. The implication, as if the crime of trafficking in human justified. In fact, the higher the blurring of crime effort, the higher the quality of the crime. Trafficking as a hidden crime is a extraordinary crime that how to prevent and fight with extraordinary waysKeywords : Trafficking, Extraordinary Crime, Covert